Versatility of the estlander flap: upper lip, lower lip and comissure reconstruction due to a dog bite - Alvarez, Natalia Haro; Grados, Jose de Jesus Orozco; Serna, Enrique Chavez; Garibay, Alejandro Lopez; Barquin, David Navarro; Carrillo, Andrea Romero; Delgado, Laura Andrade (International Journal of Research in Medical Sciences, 2019)
Background: Dog bites continue to be a frequent cause for plastic and reconstructive services in the world. The grand majority of these cases affect the head and neck area; and more often than not they involve the commissure and the lips. The latter leading to an increased level of difficulty and a substantial decrease on the posibilities for a successful reconstruction. This case report focuses on the exploration of the Abbe-Estlander flap as an efficient alternative in most of these cases. Methods: We present two clinical cases involving dog bites where the affected area of both patients was estimated to be one third of the total volume of the lip. Both patients required emergency reconstructive surgery. An Estlander flap was successfully performed in both instances. The purpose of the article is to share the results and motivate the medical community to continue to use this method as a strong avenue for an effective recovery. Results: After two months of the surgery, the team followed up with both patients and they were satisfied with the results. Patient A presented adequate healing of the wound; a lack of alignment of the mucocutaneous rim and rounding of the commissure was observed. Phonation, oral continence without any leakage and complete closure of the lip were also part of the recovery assessment. Patient B presented adequate healing of the wound, phonation and medium oral continence with occasional leakage of liquids and incomplete closure. Conclusions: The Abbe-Estlander flap is still an excellent reconstructive alternative for upper and lower lip reconstruction where the affected area is up to one third of the total volume. As long as the commissure involvement represents minimum difficulty, both aesthetic and functional objectives can be successfully attained using this flap.